PERAN PEMERINTAH DESA DALAM PROMOSI KERAJINAN GERABAH DI DESA WISATA PENAKAK KABUPATEN LOMBOK TIMUR - Lalu Moh. Nazar Fajri; M. Adib Zata Ilmam; Hamdi, Hamdi; Rohani Inta Dewi; Ririn Febrina (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Desa Masbagik Timur, also known as Penakak Village, has a long-standing reputation as the oldest village in pottery craftsmanship production in East Lombok Regency. In the past, a significant portion of the village's population relied on pottery craftsmanship as their livelihood. However, after the Bali bombing incident, pottery production experienced a decline in activity. Despite various plastic and metal products entering the market, efforts to promote pottery craftsmanship continue to be intensified by the village government, artisans, and entrepreneurs to stimulate consumer purchases and attract new customers in order to improve the community's well-being. This motivated the researcher to investigate